Role of TiO2 nanomaterial in the treatment of polluted Cauvery River water in Tiruchirappalli district, Tamil Nadu, India - R. Arulnangai; K. Thirugnanasambandham; R. Ganesamoorthy; R. Gomathi; R. Parameswari (Desalination and Water Treatment)
This study evaluates the water quality of the Cauvery River in Tiruchirappalli District, Tamil Nadu, India using advanced statistical analysis and nanotechnology-based remediation. Water samples were collected from 20 monitoring stations during the pre-monsoon period of 2021 and analyzed for key parameters, including pH (7.2–8.9), electrical conductivity (1301–2833 µS/cm), total dissolved solids (1063–2116 mg/L), biological oxygen demand (16–24 mg/L), and chemical oxygen demand (18–33 mg/L). Several stations recorded BOD and COD values exceeding the permissible limits of 3 mg/L and 10 mg/L, respectively, indicating severe pollution from agricultural runoff and industrial discharge. Principal component analysis (PCA) and factor analysis (FA) are identified nitrates, phosphates, and dissolved solids as major contaminants. TiO₂ nanoparticles were applied for photocatalytic remediation, resulting in significant reductions in EC (32 %), TDS (40 %), BOD (60 %), and COD (55 %), alongside a 45 % increase in dissolved oxygen (DO). This novel integration of nanotechnology and statistical analysis offers a sustainable and effective solution for enhancing freshwater quality and guiding future pollution management strategies.